Partial duplication of vas deferens: How important is it? - Karaman Ayse; Karaman Ibrahim; Yagiz Beytullah; Cavusoglu Yusuf (Wolters Kluwer Medknow Publications, 2010)
This study reports a 1-year-old boy with unilateral partial duplication of vas deferens, diagnosed during surgery for undescended testis. Pediatric surgeons need to be aware of this kind of anomaly in order to avoid injury to this vital structure.